UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD DENGAN MENGGUNAKAN METODE ETH PADA MATA PELAJARAN IPA - Baidowi, Nanang; Muhammad Aqil Ridwan; Nidya Chandra Muji Utami; Engga Dallion (Dharmas Education Journal (DE_Journal), 2023)
The research presented in this article takes the concept that "Everyone is a Teacher Here" to improve students' capacity for critical thinking in the subject of science. Classroom Action Research (CAR) was carried out with the participation of thirty-two students from SDN Sudimara Timur's level-A class for the fourth year. The data was compiled by a combination of observation, experimentation, and the keeping of written records. After that, the data from each cycle was evaluated by taking into account the percentage of successful attempts and expanding upon those successful attempts with conclusive findings. Students' capacities for critical thinking in science improved by 83% (which is extremely important) during the first cycle of the "Everyone is a Teacher" program, and the figure grew to 86% (which is very necessary) during the second cycle of the program. According to the data, it is possible to draw the conclusion that the children in fourth grade at SDN Sudimara Timur benefited from the method to teaching and learning known as "Everyone is a teacher here." As a consequence of this, the "Everyone is a teacher" method can be implemented in various lines of research to improve the variety and quality of learning that takes place in elementary schools.